2013
DOI: 10.1186/1559-0275-10-14
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of serum samples from chikungunya-infected patients provides insights into host response

Abstract: BackgroundChikungunya is a highly debilitating febrile illness caused by Chikungunya virus, a single-stranded RNA virus, which is transmitted by Aedes aegypti or Aedes albopictus mosquito species. The pathogenesis and host responses in individuals infected with the chikungunya virus are not well understood at the molecular level. We carried out proteomic profiling of serum samples from chikungunya patients in order to identify molecules associated with the host response to infection by this virus.ResultsProteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 71 publications
(81 reference statements)
2
32
0
Order By: Relevance
“…Both studies utilized non‐CHIKF fever patients as controls, which implies that purely fever associated changes will not be detected in the respective analysis. Only one protein, lactotransferrin, was found in common to be differentially regulated by both studies .…”
Section: Chikungunya Virus Proteome Studies: the Proteinsmentioning
confidence: 89%
See 3 more Smart Citations
“…Both studies utilized non‐CHIKF fever patients as controls, which implies that purely fever associated changes will not be detected in the respective analysis. Only one protein, lactotransferrin, was found in common to be differentially regulated by both studies .…”
Section: Chikungunya Virus Proteome Studies: the Proteinsmentioning
confidence: 89%
“… Studies are identified by the first name of the author and where required, the year (Thio ; Abere ; Dhanwani (2011) ; Dhanwani (2014) ; ; Fraisier ; Wikan ; Puttamallesh ) and the protein ID or accession number listed in the study is given. Where required the proteome (liver or brain) or technique (DIGE or iTRAQ) is also indicated.…”
Section: Chikungunya Virus Proteome Studies: the Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study identified 3505 proteins of which only 514 were present in all samples and none of these were differentially expressed . An iTRAQ approach resulted in the identification of 569 proteins of which 63 were differentially expressed . A combination of 2D‐DIGE and iTRAQ resulted in the identification of 177 differentially expressed proteins out of a total of 2686 identified proteins .…”
Section: Introductionmentioning
confidence: 99%